Dental Caries Incidence Among Children at the Dental and Oral Hospital of Universitas Muhammadiyah Semarang - Innes Dewi Noviany Bambela; Widya Hary Cahyati; Eko Farida (Universitas Negeri Semarang, 2026)
Early childhood dental caries constitutes a major public health problem in Indonesia, with an exceptionally high disease burden. Data from the 2018 National Basic Health Research (Riskesdas) reported a caries prevalence of 81.5% among children aged 3–4 years, increasing to 92.6% among those aged 5–9 years, placing Indonesia among countries with the highest prevalence globally. This study aimed to analyze risk factors associated with dental caries in children, including sex, dietary habits, toothbrushing practices, parental education level, and history of preterm birth. A case–control study design was employed at the Dental and Oral Hospital of Universitas Muhammadiyah Semarang, involving 88 children aged 3 10 years selected through purposive sampling. The case group consisted of 44 children diagnosed with dental caries based on medical records (ICD-10: K02), while the control group comprised 44 children without dental caries (ICD-10: Z01.2). Data were collected using validated questionnaires and medical records. Respondent characteristics indicated that the case group was predominantly male, aged 6–10 years, and exhibited poor dietary and toothbrushing habits. Statistical analyses were conducted using the Chi-square test and logistic regression. The results demonstrated that poor dietary habits were the most dominant risk factor for dental caries (OR = 98.967; p < 0.001), followed by toothbrushing practices, which remained statistically significant in the final model. The predictive model showed that children with poor dietary habits and inadequate toothbrushing practices had a 99.37% probability of developing dental caries. These findings underscore the importance of early screening and behavioral interventions targeting dietary practices and oral hygiene among children, supported by collaborative efforts involving parents, schools, and healthcare services to reduce the prevalence of childhood dental caries.